Tryptophan hydroxylase gene polymorphism and 5HT transporter gene promoter region polymorphism in anxiety and depressive disorder-comprehensive literature review - Mushtaq, Raheel (International Journal of Research in Medical Sciences, 2024)
Anxiety and depressive disorders are multifactorial conditions influenced by genetic and environmental factors. Research has highlighted the role of genetic polymorphisms, particularly in the tryptophan hydroxylase (TPH) and serotonin transporter or 5-HTT (5-hydroxy tryptamine transporter), which regulate serotonin, a key neurotransmitter in mood regulation. Polymorphisms in TPH1 and TPH2, enzymes involved in serotonin biosynthesis, have been linked to depression and anxiety, though findings are inconsistent. While certain TPH1 polymorphisms, like T27224C, may offer protection, TPH2 variants, such as rs1386494, have been associated with major depression in specific populations. The 5-HTTLPR (serotonin-transporter-linked promoter region shows varying associations with anxiety and depressive disorders. The short (S) allele of 5-is associated with reduced serotonin uptake, higher neuroticism, and increased risk for anxiety and depression, particularly when combined with stressful life events. However, gene-environment interactions and population differences complicate these associations, as treatment responses vary across different genotypes. Despite the inconclusive results, these studies underscore the importance of serotonergic genes in mood disorders, emphasizing the need for further research into genetic, environmental, and psychological interactions to improve understanding and treatment of anxiety and depressive disorders.